Physiological Responses of Different Aged Rice Seeds to Osmopriming with PEG 6000 - Potjana Sikhao; Chamroon Laosinwattana (My University, 2024)
The objective of this research was to compare the quality of different aged rice seed after priming. The rice seeds were deteriorated by accelerated aging method at 44 °C and relative humidity 100 %, in different periods for 0 (without accelerated aging), 1, 2, 3, and 4 days. Then, the germination of rice seeds of different ages were induced by soaking in 30% of PEG 6000 solution at room temperature for 24 hours. After that, the rice seeds were dried in a hot air oven at 35 °C for 10 hours until the moisture content was close to the initial moisture. Finally, these treated rice seeds were examined for the seed quality of various characteristics such as seed germination rate (planted in the laboratory and field conditions), germination index, speed of germination, and electrical conductivity of solution used for soaking seeds. The results showed that the electrical conductivity of all different aged seeds decreased after priming. For the field of germination and germination uniformity, it was found that the seeds with different rates of deterioration showed different responses to the priming. Aged seeds with germination rates of 12 and 33 percent germination were able to induce germination rate by 27 and 48 percent, respectively, while aged seeds with higher deterioration rate had a decreased response.
Keywords: Crop Yield and Soil Fertility